El significado subjetivo de salud de un médico indígena tradicional de Zongolica, Veracruz (2012)
ABSTRACT: Given the debate on the conceptualization of health and the current boom that have taken the traditional, alternative or complementary medicines, we offer a description of the meaning of “health” for a traditional indigenous doctor and the cultural context of the Sierra Zongolica where he lives and practices traditional medicine, this with the intention of: a) contribute to the feedback of the health concept, b) provide an overview or an alternative profile about both: the healthcare professional and the care treatment which contributes to quality and adherence to treatment, and finally c) provide arguments that could explain the failure to incorporate biomedical units in rural areas.